2014
DOI: 10.3102/0162373713517935
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Targeting of Treatment

Abstract: At an annual cost of roughly $7 billion nationally, remedial coursework is one of the single largest interventions intended to improve outcomes for underprepared college students. But like a costly medical treatment with non-trivial side effects, the value of remediation overall depends upon whether those most likely to benefit can be identified in advance. Our analysis uses administrative data and a rich predictive model to examine the accuracy of remedial screening tests, either instead of or in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(70 citation statements)
references
References 29 publications
2
68
0
Order By: Relevance
“…Further, our results demonstrate that some magnitude of students who would have been previously required to take developmental education based solely on their PERT score were successful in passing gateway math. This finding offers support to numerous other studies that have shown the benefit of using multiple measures (e.g., Ngo & Kwon, 2015; Scott-Clayton, Crosta, & Belfield, 2014). A combination of flexible cutoff scores (or bands) with multiple measures such as high school transcript information (course taking and grades) might be the best approach to developmental education placement.…”
Section: Discussionsupporting
confidence: 86%
“…Further, our results demonstrate that some magnitude of students who would have been previously required to take developmental education based solely on their PERT score were successful in passing gateway math. This finding offers support to numerous other studies that have shown the benefit of using multiple measures (e.g., Ngo & Kwon, 2015; Scott-Clayton, Crosta, & Belfield, 2014). A combination of flexible cutoff scores (or bands) with multiple measures such as high school transcript information (course taking and grades) might be the best approach to developmental education placement.…”
Section: Discussionsupporting
confidence: 86%
“…Critics highlight the fact that Black and Hispanic students are disproportionately enrolled in DE coursework (Attewell, Lavin, Domina, & Levey, 2006; Complete College America, 2012) and fail to complete the work at higher rates than their White peers (Bahr, 2010;Bailey et al, 2010). Some also question the validity of high-stakes placement tests and the arbitrary cut scores used to make DE course enrollment decisions (Scott-Clayton, 2012;Scott-Clayton, Crosta, & Belfield, 2014). Advocates of DE disagree, saying that these programs facilitate democratic equality by allowing more diverse groups of students to pursue higher education than could otherwise (Bahr, 2010).…”
Section: Dementioning
confidence: 99%
“…Research has shown the limitations of using a single, standardized instrument and its association with poor outcomes for students referred to remedial courses. For example, it is estimated that one in four test‐takers in math and one in three test‐takers in English are severely misplaced with severe under‐placements being two to six times more frequent than severe over‐placements (Scott‐Clayton, Crosta, & Belfield, ). There is an ongoing examination of the validity of placement testing, and recent studies revealed high school grade point averages were better than placement tests in predicting success in college‐level work (Belfield & Crosta, ; Hughes & Scott‐Clayton, ; Scott‐Clayton, ).…”
Section: Historical Overviewmentioning
confidence: 99%